2017
DOI: 10.1016/j.bpj.2017.10.016
|View full text |Cite
|
Sign up to set email alerts
|

pKID Binds to KIX via an Unstructured Transition State with Nonnative Interactions

Abstract: Understanding the detailed mechanism of interaction of intrinsically disordered proteins with their partners is crucial to comprehend their functions in signaling and transcription. Through its interaction with KIX, the disordered pKID region of CREB protein is central in the transcription of cAMP responsive genes, including those involved in long-term memory. Numerous simulation studies have investigated these interactions. Combined with experimental results, these can provide valuable and comprehensive under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 81 publications
(160 reference statements)
4
32
0
Order By: Relevance
“…Sugase et al have found that the association rate can be enhanced by non-native hydrophobic interactions for a much slower binding system (binding of the disordered phosphorylated kinase inducible activation domain (pKID) and the KIX domain of CBP) using NMR relaxation dispersion experiments 33 . ϕ -Value analysis has also shown the involvement of non-native interactions for the same system 49 . The enhancement of the association by non-native interactions have also been found for various systems in simulations 23 , 24 , 52 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Sugase et al have found that the association rate can be enhanced by non-native hydrophobic interactions for a much slower binding system (binding of the disordered phosphorylated kinase inducible activation domain (pKID) and the KIX domain of CBP) using NMR relaxation dispersion experiments 33 . ϕ -Value analysis has also shown the involvement of non-native interactions for the same system 49 . The enhancement of the association by non-native interactions have also been found for various systems in simulations 23 , 24 , 52 .…”
Section: Discussionmentioning
confidence: 88%
“…In this case, the formation of the native interactions will be hardly affected by the ionic strength of the solution. Therefore, the electrostatic interactions must be involved in the formation of the TC and these interactions are non-native, although non-native hydrophobic interactions can also contribute 33 , 49 . The long lifetime of TC indicates that once non-native contacts are formed between charged side chains, two molecules would stick together so that TAD rearranges and folds on the surface of NCBD without dissociation (small k − in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several IDPs were found to conform to robust two-state kinetics, displaying single exponential time courses, as well as a linear dependence on reactant concentrations under pseudo-first-order conditions, another hallmark of two-state behaviour (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). Note that apparent two-state does not imply that there are no intermediates, but that any intermediates are high-energy states, which rapidly convert to the equilibrium bound state or back to the free state.…”
Section: Cooperativity In Globular and Idp Foldingmentioning
confidence: 99%
“…The Φ value analysis represents the only experimental method available to describe the structure of a transition state and it has been employed extensively to describe the mechanism of folding of globular proteins (62,63), and lately the coupled binding and folding of IDPs (36)(37)(38)40,48,50,59,60,(64)(65)(66)(67)(68)(69)(70)(71)(72)(73). Interestingly, it has been generally observed that Φ values tend to be between zero and one, with very few cases of unusual values (i.e.…”
Section: The Structure Of the Transition State: φ Value Analysismentioning
confidence: 99%